2014
DOI: 10.1016/j.epsl.2013.12.040
|View full text |Cite
|
Sign up to set email alerts
|

Architecture of on- and off-axis magma bodies at EPR 9°37–40′N and implications for oceanic crustal accretion

Abstract: 3D multi-channel seismic imaging crustal accretion mid-ocean ridges East Pacific Rise volcanism Crustal accretion at fast-spreading mid-ocean ridges is believed to be concentrated in a narrow zone up to a few kilometers wide centered beneath the ridge axis. However, there is increasing evidence for off-axis magmatism occurring beyond this narrow zone. Here, we present 3D multichannel seismic (MCS) images from the East Pacific Rise 9 • 37-40 N extending to 11 km on the ridge flanks. In the axial region, two off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 63 publications
5
60
0
Order By: Relevance
“…The upward decrease in the initial temperature suggests that the deeper section (>2000 m) confines the temperature of melts delivered shallower. Many small-scale temperature variations in the deeper section may be attributed to vigorous convection of a large, deepseated cooling magma chamber, which, however, is against the 3-D seismic observations at EPR (e.g., Han et al, 2014). More likely, these small-scale variations indicate accumulation and in situ solidification of replenished melts in small magma bodies (e.g., tens to hundreds of meters) at various depths, as advocated by the multiple-sill model (e.g., Nicolas et al, 1988;Kelemen et al, 1997;Lissenberg et al, 2004;Maclennan et al, 2005;VanTongeren et al, 2008VanTongeren et al, , 2015Natland and Dick, 2009).…”
Section: Implications For Ocean Crust Formation At Fast-spreading Ridgesmentioning
confidence: 60%
See 2 more Smart Citations
“…The upward decrease in the initial temperature suggests that the deeper section (>2000 m) confines the temperature of melts delivered shallower. Many small-scale temperature variations in the deeper section may be attributed to vigorous convection of a large, deepseated cooling magma chamber, which, however, is against the 3-D seismic observations at EPR (e.g., Han et al, 2014). More likely, these small-scale variations indicate accumulation and in situ solidification of replenished melts in small magma bodies (e.g., tens to hundreds of meters) at various depths, as advocated by the multiple-sill model (e.g., Nicolas et al, 1988;Kelemen et al, 1997;Lissenberg et al, 2004;Maclennan et al, 2005;VanTongeren et al, 2008VanTongeren et al, , 2015Natland and Dick, 2009).…”
Section: Implications For Ocean Crust Formation At Fast-spreading Ridgesmentioning
confidence: 60%
“…Anomalously rapid cooling rates (0.372-10.2 • C/yr) at 2198-3193 m may be attributed to (1) localized hydrothermal flows induced by faults/shear zones and/or (2) small magma bodies emplaced in the colder off-axial lower crust possibly related to the brittle-ductile transition. Both are equally feasible mechanisms, but recent 3-D seismic observations at EPR (e.g., Han et al, 2014) favor the latter. Although significant uncertainties are likely involved in the thermometer of Faak et al (2013) at lower temperatures (<1100 • C; see inset in Fig.…”
Section: Implications For Ocean Crust Formation At Fast-spreading Ridgesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the main ridge-perpendicular survey acquired for 3-D imaging of crustal structure (Canales et al 2012a,b;Aghaei et al 2014;Han et al 2014), an along-axis swath survey (Carbotte et al 2013;Marjanović et al 2014;Xu et al 2014) was conducted (Fig. 1a).…”
Section: Melt Distribution Along the Eprmentioning
confidence: 99%
“…As this fit to a seismic model reflects the Nu number, the seismic model supports the choice of Nu ≈ 10 rather than significantly higher values suggested elsewhere (e.g., Cochran and Buck, 2001;Spinelli and Harris, 2011). On the other hand, Han et al (2014), based on the observation of off-axis magma lenses in regions Dunn et al (2000) expected to be cool, suggested that Dunn's model may be inaccurate. However, it is not clear what ambient thermal structure is consistent with the presence of off-axis magma lenses, as these may be anomalous, even if frequent, features.…”
Section: Constraints From the Thermal Budget Of Crustal Coolingmentioning
confidence: 86%